A delayed diagnosis: recurrent fever and beta thalassaemia. (30th September 2018) - Samarkos, Michael; Mantzourani, Marina; Nika, Christina; Kalotychou, Vasiliki
Abstract : Familial Mediterranean fever and beta-thalassaemia are two genetic disorders, with a largely common geographical distribution. However, they have not much else in common, as the first is an autoinflammatory disorder, while the other is a haemoglobinopathy. We describe a patient with known beta-thalassaemia intermedia who presented with recurrent fevers and he was diagnosed with familial Mediterranean fever 2 years later. We discuss whether there is an association between the two disorders and the cognitive biases that lead to the delay in the diagnosis of familial Mediterranean fever.